A Total systems study on Miracle Candle Factory - Agbay, Arnel R.; Arceo, Ethel S.; Baqueriza, Nikki Lou O.; Cirujales, Abigail Marie B. (College of Engineering, 2002)
This is a Total Systems Study on Miracle Candle Factory. Its main objective is to provide the company with sound recommendations for the improvement of their current system. The initial step taken in order to accomplish this was the conduct of a visit to the production facility. Aside from observing the production process as well as the procedures followed in the company, the managers were also interviewed to gather additional information that will be useful in the study. In the course of the study, the group divided the company according to its different functional departments in order to analyze the company's processes more thoroughly. These departments are, Marketing & Sales, Purchasing, Inventory & Storage, Manufacturing, Transportation & Distribution, and Customer Service. The group was able to identify problems in each of the departments such as late deliveries and lack of a marketing focus to name a few. In order determine which of the problems identified were the most critical, a rating scale was developed by the group with the following criteria: Relationship with other problems (25%), Urgency of the problem (25%), Occurrence of the problem (15%) and Overall impact on the company (35%). This criteria was developed with the help of the company, while inputs in the rating system required the use of a Stream Diagnostic Chart. Problems with a score of 8.5 were considered critical by the company and were addressed by the group. Problems related to environmental stability were also considered even though the group was not able to quantify its effects. This is due to the long-term effects of emissions on the part of the company and in compliance with government regulations. To assess the environmental effects of the company, the group made use of Life Cycle Analysis (LCA). The problems identified for the different company functions are: No Additional Entry in the Customer List, Raw Materials Stock Out, Unproductive Labor Hours, Late Delivery. The main causes of these problems were also identified and analyzed. After which, the corresponding recommendations were generated. The recommendations are: 1) the adoption of an aggressive marketing strategy, 2) the use of aggregate planning & master production scheduling and 3) the use software, (e.g. STORM) to address the problems mentioned. The total cost to be incurred if the recommendations are to be implemented amounts to Php 333,000. This amount will cover the cost of training the employees, the cost of the software to be used, as well as the marketing budget for the first year.